2016
DOI: 10.2174/1872208310666160725195516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Packaging on Shelf-life and Lutein Content of Marigold (Tagetes erecta L.) Flowers

Abstract: LDPE pack was the best design among the ten package designs, in preserving lutein content of marigold flowers and extending their shelf lives. This economically viable packaging can not only boost the export potential of this ornamental flower, but also allow utilization of nutraceutical potency of lutein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…This phenomenon of enhanced lutein content with progression of storage period could be attributed to “carotenogenesis” in the stored corn kernels, which is reported here for the first time for HKI 193‐1F variety of corn. These results are also in agreement with our previous finding on occurrence of “carotenogenesis” in African marigold flowers during senescence, wherein highest production of lutein (under experimental conditions) occurred on day 9 of storage at ambient conditions (Pal, Ghosh, & Bhattacharjee, ). In the current study, no carotenogenesis was observed in the control set during the entire storage period; rather a steady decline in lutein content was found from day 30 onward, until the end of their shelf‐lives.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This phenomenon of enhanced lutein content with progression of storage period could be attributed to “carotenogenesis” in the stored corn kernels, which is reported here for the first time for HKI 193‐1F variety of corn. These results are also in agreement with our previous finding on occurrence of “carotenogenesis” in African marigold flowers during senescence, wherein highest production of lutein (under experimental conditions) occurred on day 9 of storage at ambient conditions (Pal, Ghosh, & Bhattacharjee, ). In the current study, no carotenogenesis was observed in the control set during the entire storage period; rather a steady decline in lutein content was found from day 30 onward, until the end of their shelf‐lives.…”
Section: Resultssupporting
confidence: 93%
“…Hence in the current study, it could be stated that, low oxygen permeability (indicated by low OTR) of PP/PET/Al bags (Table ) resulted in better protection of cellular protein of the packaged samples. These findings of higher retention of cellular protein in packaged corn grits vis‐a‐vis their non‐packaged counterparts are in consonance with our previous findings on LDPE‐packaged marigold flowers (Pal et al, ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, dry packaging using polyethylene sheet controlled the microorganisms (bacterial) growth at the base of cut spikes and prevent vascular blockage and increase water uptake (Amin, 2016). In marigold flowers, low-density polyethylene packaging increased vase life up to 8 days as compared to 4 days in control packaging (Pal et al, 2016). The packaging of rose "First Red" cut stems with the polyethylene sheet and corrugated fibre board box improves flower opening, vase life and overall quality (Bhaskar and Rao, 2018).…”
Section: Discussionmentioning
confidence: 99%